String processing and information retrieval 18th international symposium, SPIRE 2011, Pisa, Italy, October 17-21, 2011 : proceedings - SPIRE 2011 Pisa, Italy) (2011; Grossi, Roberto; Sebastiani, Fabrizio; Silvestri, Fabrizio; SpringerLink (Online service). (Heidelberg Springer, 2011)
This book constitutes the proceedings of the 18th International Symposium on String Processing and Information Retrieval, SPIRE 2011, held in Pisa, Italy, in October 2011. The 30 long and 10 short papers together with 1 keynote presented were carefully reviewed and selected from 102 submissions. The papers are structured in topical sections on introduction to web retrieval, sequence learning, computational geography, space-efficient data structures, algorithmic analysis of biological data, compression, text and algorithms.
Keywords: Text processing (Computer science) -- Congresses; Information storage and retrieval systems -- Congresses; Electronic books